Effect of alternating temperature on passivation characteristics of carbon steel in chloride-free saturated Ca(OH)2 solution. (15th April 2022) - Wu, Tong; Lu, Xiangyu; Chen, Zheng; Feng, Xingguo; Zhang, Yiji; Chen, Xiangfei; Zhuang, Ning
Abstract: Passivity of carbon steel was examined in saturated Ca(OH)2 solution with different alternating temperatures. The results showed that the Fe 3+ /Fe 2+ and OH - /O 2- ratios decreased, and donor density in the passive film increased with the amplitude of temperature alternation. Cracks were observed in the film when the sample experienced a higher amplitude of temperature change. Passive films on the samples in 20–50 °C and 20–60 °C alternating temperature solution were less stable than those of their counterparts in 40 °C and 50 °C solution, respectively. Furthermore, a model was proposed to explain the degradation of passive films under alternating temperature. Highlights: Passive film formed at 20–50 and 20–60 °C was less stable and protective than that formed at 40 and 50 °C, respectively. Temperature change with the amplitude of 20 °C can't while 40 °C can cause cracks in the passive film on carbon steel. Cracks caused by high-amplitude temperature change cannot be re-passivated in a short time.